Mothers’ Knowledge of Breast Cancer and Anxiety Levels in Preoperative Patients - Hartono, Dodik (Adult Health Nursing Journal, 2025)
Background: Breast cancer is one of the most feared diseases among women due to its uncertain etiology, limited preventive measures, unpredictable disease progression, and the potential for pain and disability in advanced stages. Limited knowledge about breast cancer and surgical procedures may contribute to anxiety among patients, particularly during the preoperative period, which can negatively affect psychological readiness and clinical outcomes. Objective: This study aimed to examine the relationship between mothers’ knowledge of breast cancer and anxiety levels among preoperative breast cancer patients. Methods: A correlational study with a cross-sectional design was conducted among preoperative breast cancer patients scheduled for surgery in a central surgical unit. A total of 84 respondents were recruited using accidental sampling. Data were collected using structured questionnaires to assess knowledge levels and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety. Statistical analysis was performed using Spearman’s rho correlation test with a significance level of 0.05. Results: The analysis showed a statistically significant relationship between mothers’ knowledge of breast cancer and anxiety levels among preoperative breast cancer patients (p = 0.013), indicating that lower knowledge levels were associated with higher anxiety. Conclusion: There is a significant association between mothers’ knowledge of breast cancer and preoperative anxiety levels. Strengthening patient education through structured health counseling and standardized operating procedures may help reduce anxiety and improve psychological preparedness before surgery.